The impact of surviving bowel cancer on occupation: A scoping review. (May 2020) - Martin, Elizabeth; Hocking, Clare; Sandham, Margaret
Introduction: The number of people surviving bowel cancer is increasing globally, with many of those affected living with long-term psychological and physical sequelae that potentially disrupt occupations. Method: A scoping review – guided by Arksey and O'Malley's methodological framework – was conducted to provide an overview of what is known about the impact of having had bowel cancer on occupations, and to reveal the potential role of occupational therapy. A systematic search of four databases and a grey literature repository generated 244 results. Applying inclusion and exclusion criteria, 33 items addressing bowel cancer and occupations were selected and thematically analysed. Results: Researchers have identified six domains of occupation that are impacted by bowel cancer (social activity, physical activity, sexual activity, employment and role functioning, physical functioning, and self-care) but survivors report a distinct lack of health professional support after completion of medical treatment and being left to devise self-management strategies to accommodate the long-term effects of their cancer. Conclusion: The sequelae of bowel cancer can have a significant impact on occupational participation. There is scope for increasing and improving occupational therapy input to assist people with cancer-related loss of function to re-engage in valued occupations and improve wellbeing.